Heidi - Spyri, Johanna (Oxford University Press, 2011)
Content: I'm not going with you, Aunt Dete!" Heidi cries. "Oh yes, you are!" Dete answers. Heidi loves her home in the Swiss mountains, her grandfather, and her friend Peter, the goatherd. So when Aunt Dete takes her away to Frankfurt, she doesn't leave happily. In Frankfurt, Heidi is soon good friends with Clara Sesemann, a rich but very ill girl in a wheelchair.